Non-royal Belamin Tradition Based on Adult Education : A Phenomenological Study of Kampong Banjar Ketapang, West Kalimantan - Nabila Wardani; Sony Sukmawan (Universitas Pendidikan Mandalika, 2024)
This research aims to explore the various roles of the non-royal belamin tradition in upholding adult education principles in Kampong Banjar, West Kalimantan. The study employed a phenomenological method with a qualitative approach. Data in this study were in the form of cultural behavior, describing the beliefs, history, and equipment of the non-royal belamin tradition from specific informants, the customary leader, and the implementer. Data were collected using interviews, observation, and documentation techniques. The analysis used an interactive model with reduction stages, data presentation, and conclusion drawing. The results revealed that the non-royal belamin tradition embodied four principles of adult education: (1) Life value-based learning, (2) Experience-based learning, (3) Topic-based learning relevant to life; (4) Problem-centered learning. Notably, the noble Islamic values demonstrated in this tradition encompass religious and social values. The values with the most profound impact on adult education in this tradition were al-ukhuwah (caring) and al-munfiqun (high awareness of helping others). Through the embodiment of these solid traditional values, harmony was consistently maintained.